Ivermectin within the treatment protocol for COVID-19 in Peru: Use without scientific evidence - Lescano, Jesús (2020)
Ivermectin is one of the most widely used antiparasitic drugs in veterinary medicine. Moreover, it is used for treating many parasitosis in human medicine. However, its uncontrolled massive use is being associated to the appearance of parasitic resistance. The emergence of SARS-CoV-2, causing agent of COVID-19, has challenged health systems worldwide, forcing them to urgently work in the development of proper therapeutic protocols against such disease. In Peru, the Ministry of Health approved the addition of ivermectin within the treatment protocol for COVID-19. Aiming to collect scientific evidence that supported such decision, a systematic search was performed within scientific journals´ digital repositories and clinical trials´ databases focused on therapy against COVID-19. Until the date of submission of this article, no scientific evidence was found to support the efficacy or safety of using ivermectin as treatment against SARS-CoV-2 in humans. Solely an in vitro study was found as suggestive evidence, but its replication in people would be unlikely as it would be necessary to administer considerably higher doses of the drug than those approved for use in humans. Additionally, some clinical trials are currently assessing the addition of ivermectin in COVID-19 patients, but their results have not been published yet. Finally, this article describes both the possible consequences of the generalized misinformation regarding the use of ivermectin against COVID-19 added to the permissibility for using veterinary products containing such drug in human patients, as well as the important role of veterinarians in this situation.